2019
DOI: 10.1002/cncr.31877
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of lenalidomide plus dose‐adjusted EPOCH‐R in patients with aggressive B‐cell lymphomas with deregulated MYC and BCL2

Abstract: Background Dual translocation of MYC and BCL2 or the dual overexpression of these proteins in patients with aggressive B‐cell lymphomas (termed double‐hit lymphoma [DHL] and double‐expressor lymphoma [DEL], respectively) have poor outcomes after chemoimmunotherapy with the combination of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R‐CHOP). Retrospective reports have suggested improved outcomes with dose‐intensified regimens. In the current study, the authors conducted a phase 1 study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In clinical studies, lenalidomide exhibited promising efficacy in DLBCLs, especially in non-GCB subtype, with significantly prolonged PFS and OS, either as a single agent [ 293 ] or in combination with chemotherapies (R-CHOP and similar therapies) [ 293 , 294 ] or other regiments(rituximab or ibrutinib) [ 295 , 296 ], as well as being maintenance strategy [ 297 ]. For DHL, the response to lenalidomide plus DA-EPOCH-R is less satisfied compared to DELs in terms of disease remission, PFS, and CNS involvement [ 292 ]. The difference may be attributed to the small DHL patient group or the higher correlation between DEL and non-GCB lymphoma, which respond better to lenalidomide-based therapies [ 292 , 329 ].…”
Section: Targeted Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical studies, lenalidomide exhibited promising efficacy in DLBCLs, especially in non-GCB subtype, with significantly prolonged PFS and OS, either as a single agent [ 293 ] or in combination with chemotherapies (R-CHOP and similar therapies) [ 293 , 294 ] or other regiments(rituximab or ibrutinib) [ 295 , 296 ], as well as being maintenance strategy [ 297 ]. For DHL, the response to lenalidomide plus DA-EPOCH-R is less satisfied compared to DELs in terms of disease remission, PFS, and CNS involvement [ 292 ]. The difference may be attributed to the small DHL patient group or the higher correlation between DEL and non-GCB lymphoma, which respond better to lenalidomide-based therapies [ 292 , 329 ].…”
Section: Targeted Therapymentioning
confidence: 99%
“…For DHL, the response to lenalidomide plus DA-EPOCH-R is less satisfied compared to DELs in terms of disease remission, PFS, and CNS involvement [ 292 ]. The difference may be attributed to the small DHL patient group or the higher correlation between DEL and non-GCB lymphoma, which respond better to lenalidomide-based therapies [ 292 , 329 ]. Durable remission was observed in a DHL-BCL6 case when treated with lenalidomide following salvage chemotherapy [ 330 ].…”
Section: Targeted Therapymentioning
confidence: 99%
“…Innovative strategies are urgently needed to improve the outcomes of DEL patients. Several innovative targeted drugs, such as ABT-199 [ 39 , 40 ] (a BCL2 inhibitor that was associated with a high CR rate in patients with DEL after combination with the CHOP-based regimen in a phase I trial), lenalidomide (a targeted drug for drivers of MYC expression that was demonstrated to exhibit the safety and feasibility of lenalidomide when combined with the DA-EPOCH-R regimen in patients with DHL and DEL in a phase I study), [ 41 ] ibrutinib (a BTK inhibitor that was confirmed to improve the PFS and OS in DEL patients) [ 42 ] and several advanced immunotherapies, such as checkpoint inhibitors and cellular immunotherapies, [ 43 ] have provided a framework for future therapeutic strategies. The combination of new targeted drugs with the R-CHOP or DA-EPOCH-R regimen may show additional superiority over the conventional DA-EPOCH-R regimen in terms of survival in the future and may provide more treatment opportunities for patients with DEL.…”
Section: Discussionmentioning
confidence: 99%
“…Hypokalemia caused by rituximab administration has never been reported in the literature so far. Hypokalemia was reported as a rare adverse event of complex chemo-immunotherapy combinations for lymphoma treatment (Polprasert et al, 2011;Budde et al, 2013;Johnston et al, 2016;Godfrey et al, 2019;Shimada et al, 2020). However, none of these reports suggested a direct link between rituximab administration and hypokalemia.…”
Section: Discussionmentioning
confidence: 99%